SME Owners Rationality Perspective Digital Marketing Innovation and Sales Performance in Jombang - Atmojo, Cahyo Tri; Putra, Saiful Aminudin Al Kusuma; Asmawan, Yudhi Ferdi Andri (Fakultas Ekonomi dan Bisnis, Universitas Hasyim Asy'ari Tebuireng Jombang, 2026)
This study aims to analyze the rationality of MSME actors in making decisions regarding digital marketing strategy innovation and its impact on sales performance among MSMEs in Jombang Regency. The research employed a qualitative approach with a descriptive exploratory design. The informants consisted of dimsum culinary MSMEs, Jombang batik craft MSMEs, and bag and clothing craft MSMEs that had implemented digital marketing in their business activities. Data were collected through in-depth interviews, observation, and documentation. Data analysis used the interactive model of Miles and Huberman, including data reduction, data presentation, and conclusion drawing. The findings revealed that the rationality of MSME actors in decision-making was influenced by their ability to identify market opportunities, promotional cost efficiency, utilization of digital technology, and the need to improve business competitiveness. The digital marketing innovations implemented included the use of social media, marketplaces, live shopping, visual promotion, cultural storytelling, and collaboration with content creators. The implementation of digital marketing strategies was proven to improve sales performance through market expansion, increased consumer interaction, stronger business branding, and improved customer loyalty. This study indicates that the success of digital marketing in MSMEs is determined not only by technology adoption but also by the ability of business actors to make rational, adaptive, and innovative decisions according to market needs